2007
DOI: 10.1136/bmj.39253.577859.be
|View full text |Cite
|
Sign up to set email alerts
|

Families of patients with premature coronary heart disease: an obvious but neglected target for primary prevention

Abstract: Risk of premature coronary heart disease is increased in the families of affected patients. C K Chow and colleagues argue that targeting relatives for primary prevention would be an effective policy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…Although lifestyle counseling in the clinical setting has not been very effective (27), a recent UK report suggests that the relatives of patients admitted to the hospital for early MI constitute a group of people who may be at risk and who may be particularly motivated to make behavioral changes (18). Through modeling, the authors concluded that for every 14 patients admitted with premature MI, one additional premature MI could be avoided within 5 years among their siblings.…”
Section: Tailored Interventionsmentioning
confidence: 99%
“…Although lifestyle counseling in the clinical setting has not been very effective (27), a recent UK report suggests that the relatives of patients admitted to the hospital for early MI constitute a group of people who may be at risk and who may be particularly motivated to make behavioral changes (18). Through modeling, the authors concluded that for every 14 patients admitted with premature MI, one additional premature MI could be avoided within 5 years among their siblings.…”
Section: Tailored Interventionsmentioning
confidence: 99%
“…Despite successive recommendations for screening of firstdegree relatives of patients with premature CHD, [13][14][15][16] the EUROASPIRE II study found that only 11% of siblings and 6% of children of such patients were screened in routine practice. 17 Several risk-prediction tools incorporate family history of MI, including the PROCAM, QRISK, and ASSIGN scores, although definitions are variable.…”
Section: Clinical Perspective See P 105mentioning
confidence: 99%
“…Despite the evidence from lifetime risk estimates 36 and Mendelian randomization studies 37,38 stressing the importance of risk factor control early in life, many young genetically predisposed individuals have a high prevalence of poorly controlled risk factors and are frequently missed as candidates for cardiovascular prevention because of low 10-year risk estimates. [39][40][41] A recent report suggests that individuals with a high GRS derive greater relative risk reductions from statin therapy than those with a low GRS. 42 Therefore, given the rapid progression of atherosclerosis seen in young patients with a high GRS (especially in those who also have a FHx), the overall clinical benefit of initiating statins in young genetically predisposed individuals may be favorable.…”
mentioning
confidence: 99%